Deconditioning as main mechanism of impaired exercise response in COVID-19 survivors - Rinaldo, Rocco Francesco; Mondoni, Michele; Parazzini, Elena Maria; Pitari, Federica; Brambilla, Elena; Luraschi, Simone; Balbi, Maurizio; Sferrazza Papa, Giuseppe Francesco; Sotgiu, Giovanni; Guazzi, Marco; Di Marco, Fabiano; Centanni, Stefano (The European respiratory journal, 2021)
SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) and the related coronavirus disease 2019 (COVID-19) hit Europe in February 2020 [1], raising issues on acute phase management and, later on, the management of its long-term sequelae. Cardiopulmonary exercise testing (CPET), which is the gold standard for the evaluation of exercise capacity, is included in the list of examinations of the European Respiratory Society/American Thoracic Society task force for the follow-up of COVID-19 patients [2]. However, it is not performed in every clinical centre, as it requires specific technical skills. The objective of this observational, prospective study was to evaluate the sequelae of COVID-19 by assessing exercise performance during incremental CPET. CPET reveals only a mild impairment of exercise capacity, with preserved ventilatory and gas exchange response at 3 months follow-up in COVID-19 survivors, due to deconditioning https://bit.ly/3sI8e0Y